Single Machine Common Due Date Scheduling Problems Using Neural Network - Hamad, Abdelaziz; Sanugi, Bahrom; Salleh, Shaharuddin (Penerbit UTM Press, 2002)
This paper presents an approach for scheduling under a common due date on static single machine problem based on artificial neural network. The objective is to sequence the jobs on the machine so that the total cost be minimized. This cost is composed of the total earliness and the total tardiness cost. Neural network is a suitable model in our study due to the fact that the problem is NPhard. In our study, neural network has been proven to be effective and robust in generating optimal solutions to the problem